LOS ASESINOS DE HEMINGWAY: EL PROBLEMA DE LA ADAPTACIÓN HOLLYWOODENSE DE LA NARRATIVA DE ERNEST HEMINGWAY (Ágora UNLaR, 2019)
En el mundo globalizado, la creciente necesidad de interpretar productos transmediales choca con la relaciónasimétrica y asincrónica entre la literatura y el teatro, por un lado, y el cine, por el otro. En este trabajo tomamosla obra narrativa de Ernest Hemingway y sus adaptaciones hollywoodenses como caso testigo de algunosaspectos a considerar en las problemáticas comparaciones de este tipo. HEMINGWAY’S KILLERS: THE PROBLEM OF HOLLYWOOD’S ADAPTATIONS OF ERNEST HEMINGWAY’S FICTIONAbstractIn the global world, the growing need to understand transmedial works collides with the asymmetrical andasynchronous relation between literature and drama, on the one hand, and film, on the other. In this paper wetake Ernest Hemingway’s fiction and its Hollywood adaptations as a leading case of some aspects to beconsidered in troublesome comparisons of this type.Key words: Ernest Hemingway; film adaptation; transmedia